O Congresso norte-americano e o processo de formulação da política externa - Turner, Ivy Brasil Gonçalves (2006)
The objective of the present work was to present factors that promote congressional activism in the area of foreign policy. The work involved an analysis of the main subjects related to the participation of the United States Congress in the foreign policy-making process, the intention being to present the latest thinking in this area. As such, the work seeks to contribute to the body of research being developed on the influence of domestic factors in American foreign policy. Although information and studies in Brazil about the United States abound, this is not the case for this specific area of investigation. It should be stressed that the intention of this work was not to explain the performance of the institution through history, but rather to focus on the institutional structure of the process by which US foreign policy is formulated